2008
DOI: 10.1161/strokeaha.107.497701
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Each Lower Limb to Upright Standing in Stroke Patients

Abstract: Background and Purpose-To analyze the postural behavior of standing stroke patients: (1) To differentiate between postural impairment attributable to the neurological condition (deficits attributable to the cerebral lesion) and postural impairment attributable to new mechanical constraints caused by body weight asymmetry; (2) To assess the involvement of each limb in the postural impairment; (3) To better understand which clinical deficits underlie the postural impairment. Methods-The posturographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
125
0
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(145 citation statements)
references
References 28 publications
4
125
0
16
Order By: Relevance
“…Literatürde de bu bulguyu destekleyen, çal›flmalar bulunmaktad›r (33)(34)(35). ‹nmeli hastalarda ayakta durma postürü sa¤lam ekstremiteye daha fazla a¤›rl›k verildi¤i asimetrik bir yük da¤›l›m› ile karakterizedir (36).…”
Section: G Gi Ir Ri Ifl Flunclassified
“…Literatürde de bu bulguyu destekleyen, çal›flmalar bulunmaktad›r (33)(34)(35). ‹nmeli hastalarda ayakta durma postürü sa¤lam ekstremiteye daha fazla a¤›rl›k verildi¤i asimetrik bir yük da¤›l›m› ile karakterizedir (36).…”
Section: G Gi Ir Ri Ifl Flunclassified
“…Regarding the former, individuals with stroke generally stand asymmetrically, with more weight on the non-paretic than the paretic limb. 10 Given that the stance limb is pre-loaded, an APA may not be necessary to shift the patient's COM toward the stance limb when initiating gait with the paretic limb. Patchay and Gahéry 11 found that asymmetrical loading affected COP patterns prior to gait initiation in healthy adults, such that increased loading on the stance limb resulted in a reduced ML COP shift prior to gait initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Descarregar e transferir peso entre os hemicorpos é habilidade útil no processo de reabilitação de sujeitos vítimas de acidente vascular encefálico que adquirem hemiparesias [1][2][3][4][5][6][7] . Comumente, em hemiparéticos, a postura em pé é caracterizada por descarga de peso assimetricamente distribuída entre os hemicorpos 1,[3][4][5][6][8][9][10][11][12][13][14] .…”
Section: Introductionunclassified
“…Comumente, em hemiparéticos, a postura em pé é caracterizada por descarga de peso assimetricamente distribuída entre os hemicorpos 1,[3][4][5][6][8][9][10][11][12][13][14] . Apesar de tais sujeitos preferencialmente adotarem um padrão de assimetria que sobrecarrega o lado não afetado, na síndrome de Pusher observa-se postura assimétrica que sobrecarrega o lado afetado 15,16 .…”
Section: Introductionunclassified